Penegakan Etika Bisnis dan Tata Kelola Perusahaan dalam Pencegahan Korupsi Serta Pemulihan Kepercayaan Publik pada Perusahaan Migas Nasional - Ashilah Fauziyah; Halimah Zahrah; Yesica Maulina; Dea Wisnu Ramdani; Fajar (Indo Publishing, 2025)
Corruption cases in State-Owned Enterprises (BUMN), especially in PT. Pertamina, have had an impact on decreasing public trust in state institutions. This study aims to analyze the implementation of business ethics and good corporate governance (GCG) principles in PT. Pertamina, as well as to evaluate in preventing corruption and restoring public trust. The research method used is descriptive qualitative based on literature studies, with thematic analysis of official documents, audit reports and academic studies. The results of the study indicate that anti-corruption policies have been implemented but violations still occur due to weak internalization of ethical values ​​and inconsistencies in the implementation of good corporate governance (GCG). The integration of business ethics and good corporate governance (GCG) principles has proven to be more effective than separate implementation, because it is able to build a clean, transparent and accountable organizational culture. This study recommends strengthening a culture of integrity, ongoing training, and community involvement in supervision as a strategy to eradicate corruption in the BUMN environment.